Rogue heroes [compact disc, unabridged] : the history of the SAS, Britain's secret special forces unit that sabotaged the Nazis and changed the nature of the war - Macintyre, Ben, 1963- (Random House Audio, 2016)
Britain's Special Air Service, or SAS, was the brainchild of David Stirling, a young, gadabout aristocrat whose aimlessness in early life belied a remarkable strategic mind. Where most of his colleagues looked at a battlefield map of World War II's African theater and saw a protracted struggle with Rommel's desert forces, Stirling saw an opportunity: given a small number of elite, well-trained men, he could parachute behind enemy lines and sabotage their airplanes and war material. Paired with his constitutional opposite, the disciplined martinet Jock Lewes, Stirling assembled a revolutionary fighting force that would upend not just the balance of the war, but the nature of combat itself. He faced no little resistance from those who found his tactics ungentlemanly or beyond the pale, but in the SAS's remarkable exploits facing the Nazis in the Africa and then on the Continent can be found the seeds of nearly all special forces units that would follow.